Pengaruh Faktor Pendidikan/Pelatihan, Motivasi dan Kompensasi terhadap Kinerja Pegawai Dinas Pendapatan Daerah Provinsi Sulawesi Utara - Lapadengan, Moh. Lukmanul H; Goni, John Hein (JURNAL ILMU ADMINISTRASI (JIA), 2013)
Abstract: The purpose of this research is to analyze the influence of factors of education/training, motivation and competence towards the employees’ performances. This study used descriptive method. The population involved all civil servants at Local Revenue Office of North Sulawesi Province. The 150 samples of civil servants were selected proportionally, namely 50 people from the headquarters, and 100 people from the Local Technical Implementation Unit (UPTD). The collected data were analyzed by using multiple regression analysis to test the hypothesis. The results of the study show that education/training affected the performance of the employees at a =5%. The employees’ performances in this institution will increase by 0, 263 units when factors of education / training increase into a single unit, with condition the factors of working motivation and competence remain unchanged. The influence of working motivation of the employees towards the employees’ performances is indicated by the implementation that underwent obstacles due to minimum coordination with related technical institution. For that reason, it is suggested to raise a good coordination with related institution and the relevant authorities, among departments and sub-departments both vertically and horizontally within this institution, and to improve human resource management through the establishment of technical training of local tax management as well as other trainings pertaining to the basic tasks and functions that will ultimately improve the effectiveness of the work. Keywords: education/training, motivation, competence, and employees’ performance